Synthesis, Crystal and Electronic Structures of a Thiophosphinoyl‐ and Amino‐Substituted Metallated Ylide - Mike Jörges (Wiley-VCH, 2021)
Abstract Invited for this month's cover is the group of Viktoria H. Gessner at the Ruhr‐University in Bochum (Germany). The cover shows the structure of the newly reported, isolated metallated ylide. Due to the high negative charge at the ylidic carbon center this compound is „on fire“, but can be stabilized by smart molecular design. Structure analyses of the different alkali metal complexes combined with computational studies provide insights into the electronic structure of the compounds Read the full text of their Communication at 10.1002/open.202100187.